PENERAPAN SEARCH ENGINE OPTIMIZATION PADA PEMBERITAAN DI MEDIA SIBER - Ratih Siti Aminah, Ratih Siti Aminah; Dalimunthe, Wandira Yusniah (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2024)
The presence of the internet has changed the practice of journalistic activities in the mass media, especially cyber media. Cyber media editorial policies have also adjusted to the advancement of information technology by utilizing Search Engine Optimization (SEO). The implementation of SEO techniques in journalistic activities in cyber media is very necessary so that cyber media can survive and make it easier for the community to get information that suits their needs. Currently, cyber media has a higher attention in search engines because today's internet users will search for information through search engines every day. The purpose of this study is to find out the editorial policy of Pojoksatu.id cyber media in implementing Search Engine Optimization (SEO) in carrying out journalistic activities. The research was conducted using a qualitative approach with a descriptive nature and using the case study method. The results of the study show that the editorial policy of implementing SEO in news production in Pojoksatu.id still prioritizes journalistic principles. The resulting news products combine the needs of readers and utilize search engine technology in a balanced manner. The implementation of SEO in Pojoksatu.id includes three things. First, crawling is an automated process to collect and index data from various sources so that the news produced can be automatically read by search engines. Second, pay attention to the availability of adequate equipment so that journalistic activities can be carried out optimally and the news made by journalists can be on page one. Third, policies related to human resource development and editorial, Pojoksatu.id management continuously provides training to journalists and editors to be able to write news in accordance with SEO. Journalists and editors must be able to apply the right keywords in the news to be indexed by search engines and spread news links to social media.